Hepatitis E - epidemiology and clinical course in the largest cohort in the Czech Republic - Mihalčin, Matúš; Husova, Libuse; Vasickova, Petra; Bena, Marcel; Husa, Petr (Archives of Medical Science, 2022)
Introduction: The majority of hepatitis E (HE) reports come from Western Europe. The aim of the study was to describe the typical epidemiological and clinical characteristics of HE in the Czech Republic. Methods: A retrospective analysis of 173 patients with HE. Results: At least 90% of cases were autochthonous (HEV-3 genotype). Seventeen patients were treated with ribavirin. Five underwent liver transplants because of fulminant HE. We noted neurological symptomatology in 9 cases. Six patients developed chronic HE. Conclusions: There is a possibility of severe health complications caused by the hepatitis E virus in the Czech Republic.